2002
DOI: 10.1111/j.1151-2916.2002.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of the Structure and Properties of Cubic Spinel Nitrides

Abstract: The structure and properties of cubic spinel nitrides were investigated based on first-principles theoretical calculations. The lattice constants, bulk moduli, band structures, electronic bonding, and lattice stability of thirty-nine single and double nitrides were studied. The single spinel nitrides of the form c-A 3 N 4 (where A is a Group IVA element), except c-Hf 3 N 4 , are all semiconductors with band gaps ranging from an indirect gap of 0.07 eV in c-Ti 3 N 4 to a direct gap of 3.45 eV in c-Si 3 N 4 . Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 25 publications
(34 reference statements)
12
68
3
Order By: Relevance
“…For the Si 3 N 4 -Ge 3 N 4 system such experiments have been performed in a LH-DAC at pressures of around 20 GPa and temperatures ranging up to T > 2300 K. [47] Starting with [ 47] This result implies that at the chosen synthesis conditions solid solutions of the high-pressure spinel phases of the Si 3 N 4 -Ge 3 N 4 system are not stable. The observation of c-(Si 0.59 -Ge 0.41 ) 3 N 4 , which can be approximated as c-Si 2 GeN 4 , contradicts theoretical formation energy calculations, [48] which predict that c-Si 2 GeN 4 should be unstable or metastable while c-SiGe 2 N 4 should be stable. While the theoretical result is in line with the general understanding that Si being the smaller ion should prefer the tetrahedral A site, and Ge being the larger ion should prefer the octahedral B site, the experimental observation of the mixed phase appears to be counterintuitive.…”
Section: Static High-pressure Synthesismentioning
confidence: 89%
See 3 more Smart Citations
“…For the Si 3 N 4 -Ge 3 N 4 system such experiments have been performed in a LH-DAC at pressures of around 20 GPa and temperatures ranging up to T > 2300 K. [47] Starting with [ 47] This result implies that at the chosen synthesis conditions solid solutions of the high-pressure spinel phases of the Si 3 N 4 -Ge 3 N 4 system are not stable. The observation of c-(Si 0.59 -Ge 0.41 ) 3 N 4 , which can be approximated as c-Si 2 GeN 4 , contradicts theoretical formation energy calculations, [48] which predict that c-Si 2 GeN 4 should be unstable or metastable while c-SiGe 2 N 4 should be stable. While the theoretical result is in line with the general understanding that Si being the smaller ion should prefer the tetrahedral A site, and Ge being the larger ion should prefer the octahedral B site, the experimental observation of the mixed phase appears to be counterintuitive.…”
Section: Static High-pressure Synthesismentioning
confidence: 89%
“…[48] Of all the potential compounds, only the fol- The first three of these compounds have been shown to be insulators with small gaps, whereas the rest are all metals. [48] Obviously, the participation of 3d or 4d electrons from group IVB elements in interatomic bonding tends to make these compounds metallic. None of these materials have been synthesized so far.…”
Section: Ternary and Quaternary Spinel Nitrides And Impuritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ching et al 65), 66) suggested that only γ -Si2CN4 is stable with respect to decomposition to γ -Si3N4 and γ -C3N4. These works have shown that bulk moduli for all considered dense structures increase with increase of carbon content and reach the maximum value for binary C3N4 compound.…”
Section: Computational Studies In the Si-c-n Systemmentioning
confidence: 99%